A method for enhancing durability of a gas diffusion layer and its application

By attaching a reinforcement layer to the pore walls of the gas diffusion layer and treating it with a specific impregnation liquid, the problem of the existing gas diffusion layer being easily corroded in the fuel cell is solved, and higher durability and longer service life are achieved.

CN115440993BActive Publication Date: 2025-04-22SHENZHEN GENERAL HYDROGEN ENERGY TECH CORP LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211155271.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-22
Publication Date
2025-04-22
Estimated Expiration
2042-09-22

AI Technical Summary

Technical Problem

The existing gas diffusion layer is susceptible to corrosion by acidic and high oxygen concentration environments in the actual operation of the fuel cell, resulting in reduced conductivity and deterioration of mechanical properties, making it difficult to meet the requirements of high power density and long life of the fuel cell.

Method used

By attaching a reinforcement layer to the pore walls of the gas diffusion layer, a mixture of reinforcement agent in the impregnation liquid, a styrene butadiene rubber latex and sodium alginate is used to form a durable gas diffusion layer through ultrasonic dispersion and impregnation under the pressure plate fixture.

Benefits of technology

While ensuring that the conductivity remains unchanged, the physical attenuation and chemical attenuation resistance of the gas diffusion layer are significantly improved, and the service life of the fuel cell is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115440993B_ABST
    Figure CN115440993B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for enhancing the durability of a gas diffusion layer and its application, which at least comprises the following steps: fully attaching a reinforcing layer to the internal pore wall of the gas diffusion layer, the porosity of the gas diffusion layer to which the reinforcing layer is attached is 60-80%, the reinforcing layer is formed by drying an impregnation liquid with a concentration of 0.1-8wt%; the raw material of the impregnation liquid comprises any one of a reinforcing agent or a mixture of a reinforcing agent, a styrene-butadiene rubber emulsion, and sodium alginate; the mass ratio of the reinforcing agent, the styrene-butadiene rubber emulsion, and the sodium alginate is 1:(0.03-0.53):(0.05-0.42); the reinforcing agent comprises any one of polyvinyl pyrrolidone, urea-formaldehyde resin adhesive, polyvinyl acetate adhesive, polyacrylic acid resin adhesive, epoxy resin adhesive, and CeO2 emulsion. The durable gas diffusion layer in the present application has good physical decay resistance / chemical decay resistance while ensuring that the conductivity of the gas diffusion layer remains unchanged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fuel cells, and in particular to a method for enhancing the durability of a gas diffusion layer and an application thereof. Background Art

[0002] The key components of proton exchange membrane fuel cells include: catalyst layer, proton exchange membrane, gas diffusion layer and bipolar plate. Gas diffusion layer (GDL) is located between the catalyst layer and the bipolar plate. Its main functions are to conduct reaction gas, discharge excess water, conduct heat, conduct electrons and provide mechanical support for membrane electrode.

[0003] At present, the commonly used preparation steps of the gas diffusion layer are as follows: acrylonitrile is polymerized to obtain polyacrylonitrile, polyacrylonitrile is spun and sintered to obtain carbon fiber, the carbon fiber is chopped into short carbon fiber with a length of 10-15 mm and a diameter of 5-10 μm, the carbon fiber is surface treated, and papermaking is obtained to obtain base paper. The base paper is filled with holes and sintered to obtain carbon paper; the carbon paper is impregnated with PTFE and sintered at 350-400℃ for 30-60min, a microporous layer slurry is coated on one side of the carbon paper, and the gas diffusion layer is obtained after sintering at 350-400℃ for 30-60min.

[0004] In the actual operation of the fuel cell, since the GDL is in an acidic (low pH) and high oxygen concentration temperature and humidity environment, carbon paper corrosion will occur during long-term operation; and side reactions may also occur during the reaction of the catalytic layer, and the generated byproduct H2O2 will corrode the carbon paper particularly seriously. Some extreme situations may also occur during the operation of the fuel cell, such as emergency stop and insufficient fuel supply, which will cause the cathode of the fuel cell to generate a high potential or even a reverse pole, causing serious corrosion of the carbon material. Carbon paper corrosion will increase the resistance of the gas diffusion layer, cause PTFE to fall off, reduce hydrophobicity, and greatly reduce mechanical properties.

[0005] Therefore, with the development of fuel cell technology, the power density of fuel cells is getting higher and higher, and the life requirements are getting longer and longer, which in turn puts higher requirements on the physical / chemical attenuation resistance of the gas diffusion layer, and a gas diffusion layer with better durability is urgently needed. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a method for enhancing the durability of a gas diffusion layer and its application. The durable gas diffusion layer prepared has good physical and chemical attenuation resistance while ensuring that the conductivity of the gas diffusion layer remains unchanged. At the same time, the enhancement method of the present invention has simple steps and strong operability.

[0007] To solve the above technical problems, one of the present inventions is to provide a method for enhancing the durability of a gas diffusion layer, which comprises at least the following steps: fully attaching the reinforcement layer to the pore wall inside the gas diffusion layer, wherein the porosity of the gas diffusion layer to which the reinforcement layer is attached is 60-80%,

[0008] The reinforcing layer is formed by drying an impregnation liquid with a concentration of 0.1-8wt%;

[0009] The raw material of the impregnation liquid includes any one of a reinforcing agent or a mixture of a reinforcing agent, styrene-butadiene rubber latex, and sodium alginate;

[0010] The mass ratio of the reinforcing agent, styrene-butadiene rubber latex and sodium alginate is 1:(0.03-0.53):(0.05-0.42);

[0011] The reinforcing agent includes any one of polyvinyl pyrrolidone, urea-formaldehyde resin adhesive, polyvinyl acetate adhesive, polyacrylic acid resin adhesive, epoxy resin adhesive, and CeO2 emulsion.

[0012] Furthermore, the gas diffusion layer used in the present application is the GDL produced by Shenzhen General Hydrogen Energy Technology Co., Ltd., or other commercial GDL.

[0013] Furthermore, the impregnation liquid needs to be ultrasonically dispersed for 1-2 hours.

[0014] Furthermore, a method for enhancing the durability of a gas diffusion layer comprises the following specific steps:

[0015] S1, preparing an impregnation solution;

[0016] S2, placing the gas diffusion layer in a fixture with upper and lower pressing plates, the two pressing plates are closely attached to the upper and lower surfaces of the gas diffusion layer, and then uniformly applying a pressure of 0.5-3MPa to the surface of the gas diffusion layer; wherein the gas diffusion layer comprises a first side and a second side opposite to the first side, using a pump to sequentially introduce the impregnation liquid prepared in step S1 from the first side and flow out from the second side, t1 being the time for the impregnation liquid to flow from the first side to the second side; then introducing the impregnation liquid from the second side and flowing out from the first side, t2 being the time for the impregnation liquid to flow from the second side to the first side;

[0017] S3. After the impregnation is completed, the liquid supply is stopped and the excess impregnation liquid is discharged. Then, the fixture and the gas diffusion layer in step S2 are placed in a nitrogen environment, and the pressure is released after sintering to obtain a durable gas diffusion layer.

[0018] Furthermore, the t1 is 1-60 min; the t2 is 1-60 min.

[0019] Through the above technical solution, the impregnation time is determined by the type of impregnation liquid, the concentration of the impregnation liquid and the physical properties of the gas diffusion layer. When the viscosity of the impregnation liquid is small, which is conducive to impregnation, the interaction with the GDL is strong, and the pores of the GDL are large, and the flow rate of the impregnation liquid is large, the impregnation time is short. When the viscosity of the impregnation liquid increases, the interaction with the GDL is weak, and the flow rate of the impregnation liquid is low, the impregnation time is long.

[0020] At the same time, since the pressure plate of the fixture presses the surface of the gas diffusion layer, on the one hand, it simulates the assembly conditions in the battery, and on the other hand, it ensures that the surface of the gas diffusion layer will not be affected by the impregnation liquid, thereby ensuring its conductive performance.

[0021] Furthermore, the t1 is 20 min; the t2 is 20 min.

[0022] Through the above technical solution, the impregnation liquid can be fully dispersed inside the gas diffusion layer to ensure uniform impregnation effect.

[0023] Furthermore, in step S2, the flow rate of the impregnation liquid is 20-120 mL / min.

[0024] Through the above technical solution, the concentration of the impregnation liquid is moderate, so that the impregnation liquid can be fully diffused in the gas diffusion layer. At the same time, since the gas diffusion layer is squeezed near the pressure plate, it is difficult for the impregnation liquid here to evenly impregnate the gas diffusion layer. The addition of styrene-butadiene rubber and sodium alginate can promote the impregnation liquid to more fully fill the pores of the gas diffusion layer.

[0025] Furthermore, in step S3, the sintering temperature is 60-180° C., and the sintering time is 0.5-90 min.

[0026] Furthermore, the pressing plate is an elastic pad with a hardness of 5-60 degrees.

[0027] Furthermore, the material of the elastic pad is any one of silicone, rubber, soft polyvinyl chloride, and thermoplastic elastomer.

[0028] Furthermore, the rubber includes any one of EPDM sponge rubber, nitrile sponge rubber, silicone sponge rubber, natural rubber, and thermoplastic rubber.

[0029] Furthermore, the elastic pad is made of silicone.

[0030] The second aspect of the present invention is to propose a durable gas diffusion layer prepared by the above-mentioned method for enhancing the durability of a gas diffusion layer.

[0031] The third aspect of the present invention is to propose the application of the above-mentioned durable gas diffusion layer in a fuel cell.

[0032] In the technical solution of the present invention, the real environment of the gas diffusion layer in the fuel cell is simulated, and the conductive network of the gas diffusion layer is the same as that in the fuel cell. At the same time, the pressure plates on both sides of the gas diffusion layer use soft elastic pads, which can well cover and protect the microporous layer and the surface of the support layer of the gas diffusion layer from being impregnated by the impregnation liquid, thereby ensuring that the impregnation liquid will not affect the conductivity of the gas diffusion layer during the treatment process, that is, the conductivity of the gas diffusion layer remains unchanged before and after the impregnation liquid treatment. The technical solution of the present invention has simple steps and strong operability. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0034] Figure 1 This is a flow chart of the impregnation process of the durable gas diffusion layer in Example 1.

[0035] Figure 2 The tensile stress results of the gas diffusion layers prepared in Examples 1 and 2 and Comparative Examples 1 and 3 in the TD and MD directions are shown in FIG.

[0036] Figure 3 The through-plane resistance curves of the gas diffusion layers prepared in Example 1 and Comparative Example 1 are shown.

[0037] Figure 4 The through-plane resistance curves of the gas diffusion layers prepared in Example 2 and Comparative Example 1 are shown.

[0038] Figure 5 The through-plane resistance curves of the gas diffusion layers prepared in Example 3 and Comparative Example 1 are shown.

[0039] Figure 6 The through-plane resistance curves of the gas diffusion layers prepared in Example 4 and Comparative Example 1 are shown.

[0040] Figure 7 The through-plane resistance curves of the gas diffusion layers prepared in Example 5 and Comparative Example 1 are shown.

[0041] Figure 8 It is the through-plane resistance curve of the gas diffusion layer prepared in comparative examples 1 and 2.

[0042] Fig. 9The through-plane resistance curves of the gas diffusion layers prepared in comparative examples one and three are shown.

[0043] Fig.10 The battery performance curves of Examples 1 and 2 and Comparative Examples 1 and 3 are shown.

[0044] Fig.11 It is a battery performance curve diagram in Example 1 and Comparative Example 1.

[0045] Fig.12 It is a battery performance curve diagram in Example 2 and Comparative Example 1.

[0046] Fig.13 It is the battery performance curve diagram of comparative examples 1 and 3.

[0047] Fig.14 The battery performance curves of Example 3 and Comparative Example 1 are shown in FIG.

[0048] Fig.15 The battery performance curves of Example 4 and Comparative Example 1 are shown.

[0049] Fig.16 It is a battery performance curve diagram of Example 5 and Comparative Example 1.

[0050] Fig.17 It is the battery performance curve diagram of comparative examples 1 and 2.

[0051] Fig.18 It is a top view of the durable gas diffusion layer and the clamp in Example 1.

[0052] Among them, 1. microporous layer; 2. supporting layer; 3. upper pressing plate; 4. lower pressing plate; 5. clamp.

[0053] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0054] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials and reagents used in the following examples are all commercially available unless otherwise specified. The quantitative tests in the following examples were performed in triplicate, and the data are the average or average ± standard deviation of the triplicate experiments.

[0056] In addition, the "and / or" in the full text includes three solutions. Taking A and / or B as an example, it includes technical solution A, technical solution B, and a technical solution that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

[0057] The untreated gas diffusion layer used in Examples 1 to 5 and Comparative Examples 1 to 3 of the present application is GDL-S-16 produced by Shenzhen General Hydrogen Energy Technology Co., Ltd., denoted as GDL-0.

[0058] Embodiment 1

[0059] S1. Dilute the epoxy resin to obtain a 0.1 wt% epoxy resin impregnation solution, and disperse the solution by stirring for 30 minutes and ultrasonically dispersing the solution for 1 hour to obtain an impregnation solution.

[0060] S2, GDL-0 includes a microporous layer and a support layer. The surface of GDL-0 is provided with an upper pressing plate and a lower pressing plate which are closely attached to the surface of GDL-0. The structure is as follows: Figure 1 Place the upper and lower pressure plates and GDL-0 in the fixture, which is made of transparent acrylic material and has the following structure: Fig.18 As shown. The fixture applies pressure to the upper and lower pressing plates. At this time, the upper and lower pressing plates are subjected to a uniform pressure of 0.8MPa. Figure 1 Where P represents pressure. The gas diffusion layer comprises a first side and a second side opposite to the first side. The impregnation liquid prepared in step S1 is introduced into the gas diffusion layer from the first side and the second side in sequence. Figure 1 , 18 As shown, the direction of the hollow arrow represents the flow direction of the impregnation liquid, and t1 is the time for the impregnation liquid to flow from the first side to the second side; the flow direction of the impregnation liquid is changed, and t2 is the time for the impregnation liquid to flow from the second side to the first side. The flow of the impregnation liquid is observed through a transparent fixture to ensure a uniform impregnation effect, and t1 and t2 are both 20 minutes.

[0061] S3. Then, nitrogen was introduced, and the mixture was dried from room temperature to 100° C. at 20° C. / 10 min. The pressure was released. The obtained durable gas diffusion layer was recorded as GDL-1. The porosity of the obtained GDL-1 was 70%.

[0062] Test the through-plane resistance of GDL-1, the results are as follows Figure 3 shown.

[0063] According to the tensile strength test method in the national standard "Carbon Paper Characteristics Test Method", the tensile strength of GDL-1 was tested. The results are as follows Figure 2 shown.

[0064] GDL-1 was placed in a fixture and compressed 50 times under 30-100 kPa conditions. It was taken out and recorded as GDL-1-old-1. Two pieces of GDL-1-old-1 and CCM were packaged into a membrane electrode and assembled into a battery. The battery performance of the battery was tested at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0. Two pieces of GDL-1 and CCM were packaged into a membrane electrode and assembled into a battery. The battery performance of the battery was tested at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0. The results are as follows: Fig.10 and Fig.11 shown.

[0065] The difference between the second embodiment and the first embodiment is that:

[0066] S1. Dilute the epoxy resin to obtain an 8 wt % epoxy resin impregnation solution.

[0067] S3. Then, nitrogen was introduced, and the mixture was dried from room temperature to 100°C at 20°C / 10min, and the pressure was released. The obtained durable gas diffusion layer was recorded as GDL-2.

[0068] Test the through-plane resistance of GDL-2, the results are as follows Figure 4 shown.

[0069] According to the tensile strength test method in the national standard "Carbon Paper Characteristics Test Method", the tensile strength of GDL-2 was tested. The results are as follows Figure 2 shown.

[0070] GDL-2 was placed in a fixture and compressed 50 times under 30-100 kPa conditions. It was taken out and recorded as GDL-2-old-1. Two pieces of GDL-2-old-1 and CCM were packaged into a membrane electrode and assembled into a battery. The battery performance of the battery was tested at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0. Two pieces of GDL-2 and CCM were packaged into a membrane electrode and assembled into a battery. The battery performance of the battery was tested at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0. The results are as follows: Fig.10 and Fig.12 shown.

[0071] The difference between the third embodiment and the first embodiment is that:

[0072] S1, diluting the CeO2 emulsion to obtain a 0.1wt% CeO2 impregnation solution;

[0073] S3. Then, nitrogen was introduced, and the mixture was baked at 80° C. for 0.5 min. The pressure was released, and the obtained durable gas diffusion layer was recorded as GDL-3.

[0074] Test the through-plane resistance of GDL-3, the results are as follows Figure 5 shown.

[0075] The durability of GDL-3 was accelerated by using Fenton's reagent, and GDL-3 was completely immersed in Fenton's reagent. The Fenton's reagent was replaced every 6 hours for a total of 30 cycles. The GDL-3-old-2 was taken out and recorded as GDL-3-old-2. The two pieces of GDL-3-old-2 and CCM were packaged into a membrane electrode, and a battery was assembled to test the battery performance at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0; the two pieces of GDL-3 and CCM were packaged into a membrane electrode, and assembled into a battery to test the battery performance at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0. The results are as follows: Fig.14 shown.

[0076] The difference between the fourth embodiment and the first embodiment is that:

[0077] S1. Dilute the CeO2 emulsion to obtain 8 wt% CeO2 impregnation solution

[0078] S3. Then, nitrogen was introduced, and the mixture was baked at 80° C. for 0.5 min. The pressure was released, and the obtained durable gas diffusion layer was recorded as GDL-4.

[0079] Test the through-plane resistance of GDL-4, the results are as follows Figure 6 shown.

[0080] The durability of GDL-4 was accelerated by using Fenton's reagent, and GDL-4 was completely immersed in Fenton's reagent. The Fenton's reagent was replaced every 6 hours for a total of 30 cycles. The GDL-4-old-2 was taken out and recorded as GDL-4-old-2. The two pieces of GDL-4-old-2 and CCM were packaged into a membrane electrode, and a battery was assembled to test the battery performance at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0; the two pieces of GDL-4 and CCM were packaged into a membrane electrode, and assembled into a battery to test the battery performance at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0. The results are as follows: Fig.15 shown.

[0081] The difference between the fifth embodiment and the first embodiment is that:

[0082] S1. Dilute the CeO2 emulsion to obtain a 0.1wt% CeO2 impregnation solution, then add styrene-butadiene rubber and sodium alginate, wherein the mass ratio of CeO2, styrene-butadiene rubber and sodium alginate is 1:0.45:0.3, and prepare a hydrophobic impregnation solution after stirring and dispersing for 30 minutes and ultrasonic dispersion for 1 hour.

[0083] S3. Then, nitrogen was introduced, and the mixture was baked at 80° C. for 0.5 min. The pressure was released, and the obtained durable gas diffusion layer was recorded as GDL-5.

[0084] Test the through-plane resistance of GDL-5, the results are as follows Figure 7 shown.

[0085] The durability of GDL-5 was accelerated by using Fenton's reagent, and GDL-5 was completely immersed in Fenton's reagent. The Fenton's reagent was replaced every 6 hours for a total of 30 cycles. The GDL-5-old-2 was taken out and recorded as GDL-5-old-2. The two pieces of GDL-5-old-2 and CCM were packaged into a membrane electrode, and a battery was assembled to test the battery performance at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0; the two pieces of GDL-5 and CCM were packaged into a membrane electrode, and assembled into a battery to test the battery performance at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0. The results are as follows: Fig.16 shown.

[0086] Comparative Example 1

[0087] The gas diffusion layer is GDL-0.

[0088] Test the through-plane resistance of GDL-0. The results are as follows: Figure 3 shown.

[0089] According to the tensile strength test method in the national standard "Carbon Paper Characteristics Test Method", the tensile strength of GDL-0 was tested. The results are as follows Figure 2 shown.

[0090] GDL-0 was placed in a fixture and compressed for 50 cycles at 30-100 kPa (simulating mechanical compression attenuation during battery assembly). The GDL-0 was taken out and recorded as GDL-0-old-1. The two GDL-0-old-1 and CCM were packaged into membrane electrodes and assembled into a battery. The battery performance was tested at 100 kPa, 80°C, 100% RH and a stoichiometric ratio of 1.3 / 2.0. The results are as follows: Fig.11 shown.

[0091] The durability of GDL-0 was accelerated by using Fenton's reagent, and GDL-0 was completely immersed in Fenton's reagent. The Fenton's reagent was replaced every 6 hours for a total of 30 cycles. The GDL-0-old-2 was taken out and recorded as GDL-0-old-2. The two pieces of GDL-0-old-2 and CCM were packaged into a membrane electrode and assembled into a battery. The battery performance of the battery was tested at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0; the two pieces of GDL-0 and CCM were packaged into a membrane electrode and assembled into a battery. The battery performance of the battery was tested at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0. The results are as follows: Fig.14 shown.

[0092] Comparative Example 2

[0093] The GDL-0 was placed in a 0.1wt% CeO2 impregnation solution and baked at 80°C for 0.5min. The obtained gas diffusion layer was named GDL-6.

[0094] Test the through-plane resistance of GDL-6, the results are as follows Figure 8 shown.

[0095] The durability of GDL-6 was accelerated by using Fenton's reagent, and GDL-8 was completely immersed in Fenton's reagent. The Fenton's reagent was replaced every 6 hours for a total of 30 cycles. The sample was taken out and recorded as GDL-6-old-2. The two pieces of GDL-6-old-2 and CCM were packaged into a membrane electrode, and a battery was assembled to test the battery performance at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0; the two pieces of GDL-6 and CCM were packaged into a membrane electrode, and assembled into a battery to test the battery performance at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0. The results are as follows: Fig.17 shown.

[0096] Comparative Example 3

[0097] GDL-0 was placed in 1 wt% epoxy resin, placed in a water bath at 80°C for 40 min, and dried from room temperature to 100°C at a rate of 20°C / 10 min. The resulting gas diffusion layer was designated as GDL-7.

[0098] Test the through-plane resistance of GDL-7, the results are as follows Fig. 9 shown.

[0099] According to the tensile strength test method in the national standard "Carbon Paper Characteristics Test Method", the tensile strength of GDL-7 was tested. The results are as follows Figure 2 shown.

[0100] Place GDL-7 in a fixture and cyclically compress it 50 times under 30-100 kPa conditions. Take it out and record it as GDL-7-old-1. Package 2 pieces of GDL-7-old-1 and CCM into a membrane electrode and assemble them into a battery. Test the battery performance at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0. Package 2 pieces of GDL-7 and CCM into a membrane electrode and assemble them into a battery. Test the battery performance at 100 kPa, 80°C, 100% RH with a stoichiometric ratio of 1.3 / 2.0. The results are shown in 13.

[0101] Result analysis:

[0102] (1) GDL-0 is an untreated sample, GDL-1 and GDL-2 are prepared using the impregnation method of the present application, and GDL-7 is a gas diffusion layer obtained by full impregnation treatment with epoxy resin impregnation liquid.

[0103] Depend on Figure 2 As shown, the tensile stress of GDL-1, GDL-2 and GDL-7 in MD and TD directions are improved to a certain extent. Among them, GDL-7>GDL-2>GDL-1>GDL-0. This shows that both the impregnation method of the present application and simple impregnation can improve the tensile stress of GDL, and the tensile stress is related to the concentration of the impregnation solution.

[0104] Figure 3 , 4 and Fig. 9 As shown, GDL-1≈GDL-2≈GDL-0, that is, the conductivity of the GDL is almost unchanged after being impregnated with epoxy resin by the impregnation method of the present application, while the resistance of the gas diffusion layer after simple impregnation treatment increases.

[0105] like Fig.10 As shown, the battery performance is: GDL-1≈GDL-2≈GDL-0>GDL-7. That is, through the impregnation method of the present application, the battery performance of GDL-1 and GDL-2 fully impregnated with epoxy resin impregnation liquid is similar to that of untreated GDL-0, but its mechanical properties are greatly improved;

[0106] like Fig.11 , 12 As shown, the mechanical durability of GDL-1 and GDL-2 is also greatly improved;

[0107] like Fig.10 , 13 As shown in the figure, although the mechanical properties and mechanical durability of the gas diffusion layer were improved by a simple impregnation method with epoxy resin, the battery performance was seriously degraded.

[0108] Therefore, after the gas diffusion layer is treated by the impregnation method of the present application, its battery performance, mechanical properties, and mechanical durability are all improved.

[0109] (2) GDL-0 is an untreated sample, GDL-3, GDL-4, and GDL-5 are durable gas diffusion layers fully impregnated with CeO2 impregnation solution, GDL-5 is a durable gas diffusion layer fully impregnated with a mixed impregnation solution of CeO2 emulsion, styrene-butadiene rubber emulsion, and sodium alginate, and GDL-6 is prepared by adding CeO2 to the microporous layer slurry and coating it on the base layer.

[0110] Figure 5 , 6 As shown in Figures 7 and 8, GDL-3≈GDL-4≈GDL-5≈GDL-0>GDL-6, that is, the conductivity of GDL is almost unchanged after being impregnated with CeO2 by the patented method, while simply adding CeO2 to the microporous layer will increase the resistance.

[0111] like Fig.14 , 15 , 16, and 17, the battery performance is: GDL-3≈GDL-4≈GDL-5≈GDL-0>GDL-6. That is, through the impregnation method of the present application, the battery performance of GDL-3, GDL-4, and GDL-5 fully impregnated with CeO2 impregnation solution is similar to that of the untreated GDL-0, but their chemical durability is greatly improved, and the chemical durability of GDL-5 is improved the most; while the method of simply immersing GDL-0 in CeO2 impregnation solution, although the chemical durability is improved, its resistance and battery performance are seriously reduced.

[0112] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0113] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for enhancing the durability of a gas diffusion layer, characterized in that: At least the following steps are included: The reinforcement layer is fully attached to the pore wall inside the gas diffusion layer. The porosity of the gas diffusion layer to which the reinforcement layer is attached is 60-80%. The reinforcing layer is formed by drying an impregnation liquid with a concentration of 0.1-8wt%; The raw material of the impregnation liquid includes any one of a reinforcing agent or a mixture of a reinforcing agent, styrene-butadiene rubber latex, and sodium alginate; The mass ratio of the reinforcing agent, styrene-butadiene rubber latex and sodium alginate is 1:(0.03-0.53):(0.05-0.42); The reinforcing agent includes any one of polyvinyl pyrrolidone, urea-formaldehyde resin adhesive, polyvinyl acetate adhesive, polyacrylic acid resin adhesive, epoxy resin adhesive, and CeO2 emulsion; The specific steps include: S1, preparing an impregnation solution; S2, placing the gas diffusion layer in a fixture with upper and lower pressing plates, the two pressing plates are closely attached to the upper and lower surfaces of the gas diffusion layer, and then uniformly applying a pressure of 0.5-3MPa to the surface of the gas diffusion layer; wherein the gas diffusion layer comprises a first side and a second side opposite to the first side, and the impregnation liquid prepared in step S1 is sequentially introduced from the first side and flows out from the second side using a pump, and t1 is the time for the impregnation liquid to flow from the first side to the second side; then, the impregnation liquid is introduced from the second side and flows out from the first side, and t2 is the time for the impregnation liquid to flow from the second side to the first side; S3. After the impregnation is completed, the liquid supply is stopped and the excess impregnation liquid is discharged. Then, the fixture and the gas diffusion layer in step S2 are placed in a nitrogen environment, and the pressure is released after sintering to obtain a durable gas diffusion layer.

2. A method for enhancing the durability of a gas diffusion layer according to claim 1, characterized in that: The impregnation solution needs to be ultrasonically dispersed for 1-2 hours.

3. A method for enhancing the durability of a gas diffusion layer according to claim 1, characterized in that: The t1 is 1-60 min; the t2 is 1-60 min.

4. A method for enhancing the durability of a gas diffusion layer according to claim 1, characterized in that: In step S2, the flow rate of the impregnation liquid is 20-120 mL / min.

5. A method for enhancing the durability of a gas diffusion layer according to claim 1, characterized in that: In step S3, the sintering temperature is 60-180° C., and the sintering time is 0.5-90 min.

6. A method for enhancing durability of a gas diffusion layer according to claim 1, characterized in that: The pressing plate is an elastic pad with a hardness of 5-60 degrees.

7. A method for enhancing the durability of a gas diffusion layer according to claim 6, characterized in that: The material of the elastic pad is any one of silica gel, rubber, soft polyvinyl chloride and thermoplastic elastomer.

8. A durable gas diffusion layer, characterized in that: The gas diffusion layer is prepared by the method for enhancing the durability of the gas diffusion layer as described in any one of claims 1 to 7.

9. Use of the durable gas diffusion layer according to claim 8 in a fuel cell.

Citation Information

Patent Citations

  • Preparation method of gas diffusion layer for fuel cell

    CN114927704A